Design of Single Feed, Dual-Band Circularly Polarized Quad-Mode Slot Antenna Using Coupled Mode Theory - Mekaladevi V; Natarajamani S (IEEE Access)
In this article, a dual-band, dual-sense circularly polarized (CP) rectangular slot antenna with folded slots, fed by a microstrip line, is presented for GPS applications at 1575.4 MHz (L1) and 1227.5 MHz (L2). The excitation of the rectangular slot antenna maintains a small frequency ratio by generating two modes at closely spaced frequencies through characteristic mode analysis (CMA) and coupling mode theory (CMT). Dual circular polarization is then achieved by creating two orthogonal modes with respect to the fundamental modes by inserting two folded slots at angles of −45° and 45° relative to the tilted arm of the rectangular slot antenna. The proposed antenna has $100× 100× 1.6$ mm3 dimensions and radiates right-hand CP (RHCP) in the L1 band and left-hand CP (LHCP) in the L2 band. The measured impedance bandwidth is 3.6 % (1615-1675 MHz) for L1 and 26.7 % (1055-1380 MHz) for L2. The axial ratio bandwidth (ARBW) is observed as 3.2 % (1565-1616 MHz) for L1 and 4.04 % (1212-1262 MHz) for L2, with a maximum gain of 4.1 dBic and 3.8 dBic, respectively.